An Experimental Study of Reciprocal and Self-Check Teaching Methods to Improve Tennis Skills - Andi Syaiful; Zainal Widyanto; Nurwahidin Hakim; Ince Abdul Muhaemin Mangngassai (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. This study aims to evaluate the effectiveness of reciprocal and self-check teaching methods, which can serve as a reference or alternative solution in tennis lectures to enhance the quality of learning. Materials and methods. The study used an experimental method with a Pretest and Posttest design. The sample size matched the population, and individuals were paired based on their tennis ability. The t-test was used for analysis and showed a significant difference between the two groups. Conclusion. Without a doubt, the evidence suggests that the reciprocal teaching method is vastly superior to the self-check method. By incorporating a collaborative approach, reciprocal teaching enables individuals to learn from one another and to engage in active discussions. On the other hand, self-checking lacks the interactive element that is crucial for effective learning. Therefore, it is not surprising that the results overwhelmingly favor the reciprocal teaching method as the more influential and successful approach.